Adolescents, Online Gambling, and Moral Deviance: A Phenomenological Study in an Urban Environment in Medan, North Sumatra - Lubis, Mhd. Habibi; Lubis, Lahmuddin (TEMALI : Jurnal Pembangunan Sosial, 2025)
This study aims to examine adolescents’ involvement in online gambling practices and its impact on moral degradation by tracing its causal factors and the forms of deviant behavior that emerge. The urgency of this research is based on the widespread accessibility of online gambling among teenagers and the weakening of social control in the digital era. A qualitative method with a descriptive phenomenological approach was employed. Data were collected through in-depth interviews with six male adolescents in Pahlawan Subdistrict, Medan Perjuangan District, Medan City, and analyzed using an interpretative phenomenological approach. The findings reveal that adolescents’ engagement in online gambling is driven by peer influence, easy access to digital technology, interest in sports and the illusion of control, compulsive and addictive behavior, and as a form of escape from psychological pressure and boredom. Gambling activities are financed through pocket money, parental allowances, and even the sale of personal belongings. The primary impact of this practice is moral degradation, manifested in habitual lying, manipulating parents, incurring debts under false pretenses, and stealing or pawning goods. This study contributes to the discourse on adolescent deviant behavior by highlighting often-overlooked moral and social dimensions. The findings also carry important implications for youth protection policies, value-based digital literacy enhancement, and social interventions involving families, schools, and communities. The originality of this research lies in its focus on the moral experiences of adolescent online gamblers in a specific urban local context, which has rarely been explored in previous studies.